РІВЕНЬ ОСВІТИ СІЛЬСЬКОГО НАСЕЛЕННЯ ПІВДНЯ УКРАЇНИ У 60ñ80-ті рр. XX ст. (Zaporizhzhia Historical Review, 2021)
Тhe main index of ethnosocial development is undoubtedly the educational level of people. The education level of the representation of different ethnic groups is one of the principal indices of their social development.